'THOROUGHLY CHINESE': REVEALING THE PLANTS OF THE HONG MERCHANTS' GARDENS THROUGH JOHN BRADBY BLAKE'S PAINTINGS. (2nd March 2018) - Richard, Josepha; Woudstra, Jan
Abstract : The paintings in the John Bradby Blake collection should be admired for their sophisticated artistry and accurate depiction of botanical features, but they are also significant because they reveal the diversity of plants grown in the gardens of Chinese in Guangzhou (Canton). They therefore provide a precious insight into a relatively neglected topic in Chinese garden history, namely the cultivation of plants in gardens. This paper identifies one of the gardens from which the plants depicted by John Bradby Blake might have come, and looks at how those plants were used and appreciated in their Chinese context.